Pomen gozda za ohranjanje biodiverzitete dvoživk (Amphibia) na območju načrtovanega regijskega parka Kočevsko-Kolpa - Poboljšaj, Katja (Zbornik gozdarstva in lesarstva, 2000)
Of the 47 localities, 13 species of amphibians were recorded in the planned Kočevsko-Kolpa Regional Park between Spring 1999 and Autumn 2000. The larger wetlands, such as Ribnica and Rina river vallezs, the surroundings of KočevskaReka and Mlaka bz Kočevska Reka, are the most important breeding sitesfor amphibians in the studz area. Therefore these habitats are of great importance for the conservation of the biodiversitz of the amphibians in the forests of the whole area of the planned Kočevsko-Kolpa Regional Park.
Keywords: biodiversity; biotska raznovrstnost; diverziteta; dvoživke; forest; gozd; mokrišča; regijski parki; Slovenia; Slovenija; živalstvo